Stuck in the middle with you: The transaction costs of corporate employees hiring freelancers - Lustig, Caitlin; Rintel, Sean; Scult, Liane; Suri, Siddharth (CSCW2020, 2020)
Corporations are increasingly empowering employees to hire on-demand workers via freelance platforms. We interviewed full-time employees of a global technology company who hired freelancers as part of their job responsibilities. While there has been prior work describing freelancers’ perspectives there has been little research on those that hire them, the “clients”, especially in the corporate context. We found that while freelance platforms reduce many administrative burdens, there are number of conditions in which using freelance platforms in a corporate context creates high transaction costs and power asymmetries that make it difficult for clients to negotiate work rights and responsibilities. This leads corporate employee clients to feel “stuck in the middle” between their employer, the platform, and the freelancer. Ultimately, these transactions costs are a potential barrier to wider adoption. If corporations want to leverage the value of the freelance economy then better guardrails, guidelines, and perhaps even creative technology solutions will be needed.